Subjective measures to evaluate speech intelligibility, quality and difficulty in rooms for young and elderly listeners - Sato, Hiroshi (Canadian Acoustics, 2002)
The subjective measures to evaluate the speech intelligibility, word recognition, objective acoustical measures and easiness of speech perception were described. The studies were carried out in simulated sound fields and evaluated using multi dimensional scaling analysis (MDS). The studies compared the characteristics of elderly listeners and young listeners for each measure.